IDENTIFYING THE RIGHT OF A PERSON AGGRIEVED BY A PUBLIC AUTHORITY IN THE ROMANIAN CONSTITUTION AND IN COMPARATIVE LAW - Cătălin-Radu PAVEL (Challenges of the Knowledge Society)
The purpose of the present study is to analyze the development and the evolution of the right of a person aggrieved by a public authority in the Romanian Constitutions and in comparative law. The objectives of the study were to analyze the Romanian Constitutions in order to identify the provisions regarding the fundamental right of a person aggrieved by a public authority and to analyze the provisions of this fundamental right in the constitutions of other states: the Constitution of the French Republic, the constitutional Acts of the United Kingdom of Great Britain and Northern Ireland, the Fundamental Law for the Federal Republic of Germany, the Constitution of the Republic of Italy, and the Constitution of Spain. By granting the fundamental right of a person aggrieved by a public authority is ensuring a good administration of the state by giving the citizens a compliance with their legitimate rights. The citizen may be aggrieved in his legitimate rights and interests by a public authority, by means of an administrative act or by failure of a public authority to solve his application within the lawful time limit. The Romanian organic law that stipulates and protect this right is the administrative litigation law number 554/2004. Also, the Romanian state is liable for any prejudice caused as a result of judicial errors